Citra Kota Padang Dalam Puisi Padang Kota Tercinta Dan Perjalanan Senjakala Karya Leon Agusta (Tinjauan Semiotika Riffaterre) - Fadhillah Hayati; Ivan Adilla; Koko Sudarmoko (Puitika, 2023)
One of the nicknames for Padang City is Padang Kota Tercinta. This name was born from a poem by Leon Agusta. Leon Agusta's poems that contain Padang Kota Tercinta, namely the poems entitled "Padang Kota Tercinta" and "Perjalanan Senjakala". To explain the meaning and image of Padang City in the two poems, this research was conducted using semiotic theory and methodology proposed by Riffaterre, namely heuristic and hermeneutic reading. Based on the research that has been conducted, it is concluded that the matrix in the poem "Padang Kota Tercinta" is the image of Padang City struggling in the transition of modern times, and the matrix of the poem "Perjalanan Senjakala" is the image of Padang City struggling in the name of the love of Padang Kota Tercinta. Both poems reveal the changes of Padang City as it develops towards Modern Civilisation as its image. The dynamics of people's lives that begin to change, from traditional to modern, are tied to the Padang City area and the nickname of Padang Kota Tercinta. These two poems are related through the similarity of the lyricist who is referred to in the poem as The Wanderer. From his wanderings, the dynamics of human life are told as a form of love for Padang City.Keywords: Poems, Image of Padang City, Leon Agusta, Riffaterre's Semiotics, and Love.